On the resistance to extinction of fear conditioned to angry faces - Rowles, M.; Lipp, Ottmar; Mallan, K. (2012)
The present study investigated whether, like fear conditioned to pictures of snakes and spiders, fear conditioned to angry faces resists extinction even after verbal instruction and removal of the shock electrode. Participants were trained in a differential Pavlovian fear conditioning procedure with angry face or happy face conditional stimuli (CSs). Prior to extinction, half the participants in each group were informed that no more unconditional stimuli would be presented and the shock electrode was removed. In the absence of this manipulation, participants showed resistance to extinction after training with angry face CSs, but not after training with happy face CSs. Instructed extinction and electrode removal abolished fear conditioning regardless of the emotion expressed by the CS faces. This finding suggests that fear conditioned to angry faces, like fear conditioned to racial out-group faces, is more malleable than fear conditioned to snakes and spiders. © 2011 Society for Psychophysiological Research.